To determine which expression is not equivalent to \(4x + 5x + 6x + 9\) under the Commutative Property of addition, let's first simplify the original expression:
\[ 4x + 5x + 6x + 9 = (4 + 5 + 6)x + 9 = 15x + 9 \]
Now let's compare each of the provided options to see if they simplify to \(15x + 9\):
-
\(6x + 9 + 5x + 4x\): This can be rearranged to \(6x + 5x + 4x + 9 = (6 + 5 + 4)x + 9 = 15x + 9\) (Equivalent)
-
\(4 + 5x + 6x + 9x\): This is \(4 + (5 + 6 + 9)x = 4 + 20x\) (Not equivalent)
-
\(4x + 6x + 5x + 9\): This can be rearranged to \(4x + 6x + 5x + 9 = (4 + 6 + 5)x + 9 = 15x + 9\) (Equivalent)
-
\(9 + 4x + 5x + 6x\): This can be rearranged to \(9 + 4x + 5x + 6x = 9 + (4 + 5 + 6)x = 9 + 15x\) (Equivalent)
The only expression that is not equivalent to \(4x + 5x + 6x + 9\) is:
\(4 + 5x + 6x + 9x\).